Hairball-Like Migration of “Onyx Threads” into the Draining Vein during Transarterial Embolization of a Dural Arteriovenous Fistula: A Case Report and Experimental Validation - Tetsuya Ioku; Tomotaka Ohshima; Mao Yokota; Naoki Matsuo; Shigeru Miyachi (Neurointervention, 2023)
Transarterial embolization using Onyx is a well-established treatment for dural arteriovenous fistulas (DAVFs). However, complications can arise when Onyx migrates into the venous side, impairing the draining veins. We encountered a case where Onyx, injected through the arterial side, strayed into the jugular vein, forming a hairball-like structure. Our study aimed to investigate the underlying mechanism of this unusual phenomenon. We postulated that Onyx precipitates into thread-like shapes when passing through extremely narrow openings. To test this, we extruded Onyx from a syringe through a 27-gauge needle into a silicone tube with flowing water. By varying the flow speed, we observed the hardening behavior of Onyx. Under slow flow, the extruded Onyx quickly solidified at the needle tip, forming a round mass. Conversely, high-speed flow resulted in Onyx being dispersed as small pieces. We successfully replicated the formation of “Onyx threads” under continuous slow flow conditions, similar to our case. This phenomenon occurs when Onyx unexpectedly migrates to the draining vein through a tiny opening during transarterial embolization for arteriovenous shunt diseases. Early recognition and appropriate measures are necessary to prevent occlusive complications in the draining veins and the pulmonary system.